Oxitocin a szkizofrénia kezelésében mítosz vagy csoda? - Plesz Szonja Bianka (Móra Akadémia, 2023)
Schizophrenia is a complex mental disorder affecting 1% of the population. It is characterized by abnormal behavior, cognitive deficits, and hallucinations. The underlying pathological changes have not been completely discovered yet. However, it is hypothesized that the imbalance of the neurotransmitter systems like dopaminergic, serotonergic, glutamatergic, or cholinergic neural pathways are involved in the etiology of schizophrenia. There is growing evidence that the alteration of the oxytocinergic system also plays a role in its development. Moreover, several studies proved that the antipsychotic treatment combined with intranasal oxytocin could improve symptom severity. This minireview focuses on how the neurohormone oxytocin is related to schizophrenia.